2005
DOI: 10.1158/1078-0432.ccr-04-1919
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Prostate Cancer by Quantitative Analysis of Telomerase Activity

Abstract: Purpose: Prostate cancer is the most common male malignancy and the second leading cause of male cancer death; therefore, there is urgent necessity for noninvasive assays for early detection of prostate cancer. Obtaining prostate tumor samples surgically is problematic because the malignancy is heterogeneous and multifocal and early-stage tumors are nonpalpable. In contrast, exfoliated cells represent the cancer status of the entire gland better due to the general tendency of cancer cells to exfoliate into bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Blocking telomerase activation by anti-androgen and MSA through suppressing AR signaling could thus represent an effective and selective treatment modality to target prostate cancer cells. In addition, hTERT/telomerase could be measured in blood and urine (49,50), and therefore could serve as a non-invasive, tumor-specific, functionally relevant molecular biomarker for monitoring the efficacy of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking telomerase activation by anti-androgen and MSA through suppressing AR signaling could thus represent an effective and selective treatment modality to target prostate cancer cells. In addition, hTERT/telomerase could be measured in blood and urine (49,50), and therefore could serve as a non-invasive, tumor-specific, functionally relevant molecular biomarker for monitoring the efficacy of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[137][138][139][140] Quantitative assays for the detection of these genes in serum could serve as potentially valuable tools. Antibody array profiling has also identified possible serum markers, such as thrombospondin-1, that may differentiate between benign and malignant disease.…”
Section: Pca3mentioning
confidence: 99%
“…Noteworthy, the intensity of telomerase activity in tumor specimens directly relates to tumor cell growth and invasiveness, thus parallelling, at least in certain tumor types, the different stages of cancer progression (2,6,9,21,22). In addition, telomerase appears to distinguish benign hyperplasia from cancer (23,24). Previous studies indicated that active telomerase is present in lesions from AIDS-KS (12), an angioproliferative disease which can evolve into an aggressive sarcoma (10).…”
Section: Discussionmentioning
confidence: 99%